Antifungal activity of grey alder bark extractives against wood rotting fungi - Gordana Petrović; Mimica Stefanović; Milica Rančić; Milenko Mirić; Grmuša Ivana Gavrilović (Zaštita Materijala)
The effect of the treatment of beech tree (Fagus sylvatica ssp. Moesiaca) with grey alder (Alnus incana (L.) Moench) bark extractives on the improvement of its natural resistance against two rot fungi: Trametes versicolor, causative agent of white rot and Coniophora puteana, the cause of the brown rot of the tree, is investigated in this paper in laboratory conditions. Four types of extractives were used: ethyl acetate (A), ether (B), ethanol (C) and aqueous (D), obtained by ultrasonic extraction (UZE) and prepared at three concentrations of 0.5, 1.0 and 2.0 mg/ml in methanol as a solvent. The results of the study show that the highest antifungal efficiency was obtained using ethyl acetate extract at a concentration of 2.0 mg/ml. Grey alder bark extract can be a potentially environmentally friendly tool in preventing the protection of deciduous wood along with further research.